2017
DOI: 10.1016/j.anifeedsci.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Available energy content, nutrients digestibility of chili meal and effects on performance of growing pigs

Abstract: HighlightsChili meal is classified as a roughage due to its high dietary fiber content.Chili meal has moderate DE, ME and nutrients digestibility for growing pigs.Addition of chili meal have adverse effect on ADG and ATTD of nutrients.The combination of 50 g/kg chili meal and proper soybean has no significant negative effects for growing pigs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In the current study, the nutritional value of the feed, determined through proximal analysis and digestibility tests, has allowed results to be obtained for use in guinea pig diet formulation ( Castro et al, 2017 , 2018 ; Witkowska et al, 2017 ; Sánchez-Macías et al, 2018 ), as reported in other animal species ( Fortes et al, 2010 ; Safwat et al, 2015 ; Stergiadis et al, 2015 ; Fan et al, 2017 ). The DM content of feeds, their proximal composition, and digestibility varies according to different factors, such as the species of grass, plant parts, cutting age, type, and origin of the feed, whether it is of animal or plant origin ( Gadberry, 2015 ).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In the current study, the nutritional value of the feed, determined through proximal analysis and digestibility tests, has allowed results to be obtained for use in guinea pig diet formulation ( Castro et al, 2017 , 2018 ; Witkowska et al, 2017 ; Sánchez-Macías et al, 2018 ), as reported in other animal species ( Fortes et al, 2010 ; Safwat et al, 2015 ; Stergiadis et al, 2015 ; Fan et al, 2017 ). The DM content of feeds, their proximal composition, and digestibility varies according to different factors, such as the species of grass, plant parts, cutting age, type, and origin of the feed, whether it is of animal or plant origin ( Gadberry, 2015 ).…”
Section: Discussionmentioning
confidence: 80%
“…Experiments were conducted with guinea pigs housed individually in metabolic crates equipped with an individual feeder and a nipple drinker ( Castro et al, 2017 , 2018 ). The ingredients that were used as unique dietary components, in “in vivo” direct digestibility tests ( Safwat et al, 2015 ; Fan et al, 2017 ), were fodder and agricultural and kitchen waste. Protein and energy meals were included in 10% of a reference ration based on barley flour and their digestibility coefficients were determined by the difference method, considering that the indigestibility of barley flour is the same when combined with the experimental feed ( Fan et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Gross energy was determined by measuring the heat of combustion in the samples, using a bomb calorimeter (ZDHW-8, Haotian Electric Co., Ltd., Guangdong, Zhongshan, China). Acid-insoluble ash (AIA) contents of fodder and feces were determined using the method of Fan et al 25 The apparent tract digestibility of protein and gross energy was calculated using the following formula: apparent tract digestibility (%) 100 (% AIA in fodder/% AIA in feces) (% nutrient in feces/% nutrient in fodder) 100…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that plant extracts could be used to alleviate negative impact from weaning stress and improve performance in weaned pigs via improving nutrient digestibility, anti-inflammatory function and antioxidant status ( Kong et al., 2007 ; Huang et al., 2012 ; Liu et al., 2011 ; Long et al., 2019 ). Fan et al. (2017) has reported that dietary supplemented with chili meal (containing capsaicin) together with soybean oil could enhance the ADG in growing pigs, but its effect on weaned pigs and possible mechanism remained to be studied.…”
Section: Discussionmentioning
confidence: 99%